Zinc Competition among the Intestinal Microbiota - Lindsay M. Gielda (American Society for Microbiology, 2012)
ABSTRACT Bioavailable levels of trace metals, such as iron and zinc, for bacterial growth in nature are sufficiently low that most microbes have evolved high-affinity binding and transport systems. The microbe Campylobacter jejuni lives in the gastrointestinal tract of chickens, the principal source of human infection. A high-affinity ABC transporter for zinc uptake is required for Campylobacter survival in chicken intestines in the presence of a normal microbiota but not when chickens are raised with a limited microbiota. Mass spectrometric analysis of cecal contents revealed the presence of numerous zinc-binding proteins in conventional chicks compared to the number in limited-microbiota chicks. The presence of a microbiota results in the production of host zinc-binding enzymes, causing a growth restriction for bacteria that lack the high-affinity zinc transporter. Such transporters in a wide range of pathogenic bacteria make them good targets for the development of broad-spectrum antimicrobials. IMPORTANCE Zinc is an essential trace element for the growth of most organisms. Quantities of zinc inside cells are highly regulated, as too little zinc does not support growth, while too much zinc is toxic. Numerous bacterial cells require zinc uptake systems for growth and virulence. The work presented here demonstrates that the microbiota in the gastrointestinal tract reduces the quantity of zinc. Without a high-affinity zinc transporter, Campylobacter jejuni, a commensal organism of chickens, is unable to replicate or colonize the gastrointestinal tract. This is the first demonstration of zinc competition between microbiota in the gastrointestinal tract of a host. These results could have profound implications in the field of microbial pathogenesis and in our understanding of host metabolism and the microbiota.